(3TQM GdcGajIs - (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s
(3ChdgG (B:s
(3GdcdeI eHJOC hGddGe ajgG dJYQja GdLfS, Cj dJYjjf GdeGgjI dCf GdMO GdHjGf GdeGgjI dG dJYQja LejY GdCaQGO ef MjK GdEaQGO s
(3BNQgG (B:s
(3hGdJbOjQ Gdfhf GdJj aJM GdMQa GdPj KHJ bHd Gdfhf GdeNaaI JbdH Jdc Gdfhf CdakG YfO Gdhba dJCNjQgG eY GdJfhjf Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B183s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B198 s
Keywords: (3GdfMhs